1983
DOI: 10.1107/s0021889883010675
|View full text |Cite
|
Sign up to set email alerts
|

The growth and perfection of crystals of ammonium dihydrogen orthophosphate, NH4H2PO4. I. Dislocation characterization in self-nucleated crystals

Abstract: A combined theoretical analysis and experimental study has been made of the nature of dislocations which propagate in the prismatic and pyramidal growth sectors of ammonium dihydrogen phosphate (ADP). In general the line energies of the dislocations formed in both the sectors are less than 45 eV nm-~. A few higher-energy dislocations (123 eV nm-1) were characterized in the prismatic sectors. The line directions of dislocations which are formed in the pyramidal sectors are such that they propagate towards the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In fact, the most commonly occurring dislocation type is that of highest line energy. Dislocations with large line energies have also recently been observed in single crystals of ammonium dihydrogen orthosphosphate (Bhat, Roberts & Sherwood, 1983). These observations suggest that the line energy of a given dislocation is not necessarily the controlling factor in determining whether or not the dislocation occurs.…”
Section: Basic Growth-induced Dislocation Structurementioning
confidence: 90%
“…In fact, the most commonly occurring dislocation type is that of highest line energy. Dislocations with large line energies have also recently been observed in single crystals of ammonium dihydrogen orthosphosphate (Bhat, Roberts & Sherwood, 1983). These observations suggest that the line energy of a given dislocation is not necessarily the controlling factor in determining whether or not the dislocation occurs.…”
Section: Basic Growth-induced Dislocation Structurementioning
confidence: 90%
“…They were proposed more than 30 years ago for nonlinear optical applications [see for instance Moritani et al (1983)]. Their structural characterization, performed by X-ray topography, has confirmed that the crystals are characterized by high crystal perfection (Deslattes et al, 1966;Bhagavannarayana et al, 2006;Bhat et al, 1983), nearly dislocation free and free of inclusions.…”
Section: Introductionmentioning
confidence: 99%
“…In general, transition metals used as impurities incorporate predominantly into the prismatic sectors of ADP. The changes of strain and defect content caused by incorporation of impurities can be easily observed by x-ray transmission topography and correlated with growth rate since the defect structure of this sector is quite simple [12].…”
Section: Introductionmentioning
confidence: 99%